A NOVEL PROFILE’S SELECTION ALGORITHM USING AI - BELLO, Mario; LUNA, Alejandra; BONILLA, Edmondo; HERNANDEZ, Crispin; PEDROZA, Blanca; PORTILLA, Alberto (Applied Computer Science, 2020)
In order to better understand the job requirements, recruitment processes, and hiring processes it is needed to know the people skills. For a recruiter this entails analyzing and comparing the curricula of each available candidate and determining the most appropriate candidate that the activities that are required by the position. This process must be carried in the shortest length of time possible. In this paper, an algorithm is proposed to identify those candidates, either workers or college graduates.